On the political economy of high skilled migration and international trade - Spiros Bougheas; Douglas R. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2012)
We develop a two-country, two-sector model with a continuum of workers to address the link between migration and trade where policy is determined by a simple referendum. In particular, we address two questions. First, are states already in free trade areas more likely to support full integration than states without free trade? Second, is trade liberalization more likely to be supported by a simultaneous referendum on trade and migration than in one on trade alone? The key to our analysis is the recognition that for free trade, migration, or trade and migration to be adopted, the relevant policy must pass the referendum in both countries. We identify conditions under which that occurs. Our model provides an interpretation of the evolution of the politics of economic integration related to NAFTA and European Union.
Keywords: F15; F22; F59; 330; skilled labor; migration; trade; political economy; Hochqualifizierte Arbeitskräfte; Brain Drain; Außenhandelsliberalisierung; Public Choice; Wirtschaftsintegration; Theorie; NAFTA-Staaten; EU-Staaten